HYDROTHERMAL MINERALIZATION IN JAILOLO WATERS, WEST HALMAHERA, NORTH MALUKU PROVINCE - Lili Sarmili (BULLETIN OF THE MARINE GEOLOGY, 2015)
Halmahera Island tectonically is divided into two main regimes, those are East Arm Regime (EAR) and West Arm Regime (WAR). Both regimes have very different characteristics where the EAR consists of Cretaceous ultramafic rocks and old red shale, while the WAR composed of Neogene sediment. The study area is an area with active tectonism shown by recent seismic activities and volcanic eruptions. Hydrothermal activity is indicated by rocks alteration of andesite, dacite, and diorite such as kaolinite, argilic and montmorilonite. Primary metal type mineralization occured in a strong altered volcanic rocks, while the secondary mineralization occured in the sedimentary placer. AAS, petrographic analysis, and mineralografi obtained mineral pyrite, manganese, chalcopyrite in rocks from coastal and marine offshore up to depth of 100 meters. Analysis of the 36 examples of seabed sediments, showed the presence of anomalous metal minerals of Au, Cu, Mn, and Fe those are content of Au 0.01 - 0.03 ppm; Cu 14-150 ppm; Mn 23-1050 ppm; and Fe 2-10%.Keywords: Jailolo waters, western arm regime (WAR), andesite, dacite and diorite intrusion rocks, mineralization of Au, Cu, Mn, and Fe. Pulau Halmahera tektonik dibagi menjadi dua rezim utama, yaitu East Arm Rezim (EAR) dan Westt Arm Rezim (WAR). Kedua rezim memiliki karakteristik yang sangat berbeda yang EAR terdiri dari batuan ultrabasa Kapur dan shale merah tua, sedangkan WAR Terdiri dari batuan sedimen berumur Neogen. Daerah penelitian sebagai daerah dengan tektonik dan vulkanik aktif yang ditunjukan dengan aktifitas gempa dan letusan gunungapi hingga sekarang. Aktifitas hidrothermal ditunjukkan oleh alterasi pada batuan andesit, dasit, dan diorite. Mineral ubahan yang terbentuk kaolinit, argilik dan montmorilonit. Tipe mineralisasi logam primer terdapat dalam batuan vulkanik terubah kuat, sedangkan mineralisasi sekunder terdapat dalam sedimen plaser. Hasil analisis AAS, petrografi, dan mineralografi didapatkan mineral pirit, mangan, kalkopirit pada batuan di pesisir dan laut lepas hingga kedalaman 100 meter. Hasil analisis terhadap 36 sedimen dasar laut, menunjukan adanya kandungan mineral logam Au,Cu, Mn, dan Fe dengan kadar Au=0.01 - 0,03 ppm; Cu 14-150 ppm; Mn 23-1050 ppm; dan Fe 2-10% . Kata kunci: Mandala lengan barat (MLB), batuan intrusi andesit, dasit, dan diorit, mineralisasi Au, Cu, Mn, dan Fe, Perairan Jailolo, Halmahera Barat.